Assistance in Making Business Legality or NIB for MSME Owners Through Online Single Submission (OSS) in Wonorejo Village - Elvira Dewanti Libragiantari; Delta Diva Dinanty; Bayu Priambodo (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
Community service activities related to assisting in making business legality or Business Identification Number (NIB) are carried out for MSME owners in RW 07, Wonorejo Village. The purpose of this community service activity is to increase the equity of ownership of business legality or NIB. The service implementation method is divided into four stages. The first stage of MSME observation was carried out through interviews with the Head of RW 07 to obtain MSME data that did not yet have an NIB. The second stage is the survey and data collection for MSMEs which is carried out online via the Google form by distributing questionnaires on the Whatshap of MSME owners. The third stage is MSME counseling about NIB to provide an understanding of the importance of business legality or NIB. The fourth stage is assistance in making business legality or NIB online through Online Single Submission (OSS). To make it easier for MSME owners to obtain the legality of their business, assistance is carried out by visiting the residence of each MSME that will be assisted. The results that have been achieved from this community service activity are (1) there is an increase in the understanding of MSME owners in RW 07, Wonorejo Village about the importance of a business legality or NIB and the many benefits that can be obtained by owning an NIB; (2) understanding of information related to the process of making NIB through OSS; and (3) even distribution of NIB ownership levels. It is known that the 4 assisted MSMEs already have NIB with the help of this community service activity.